Diluted Bitumen: Physicochemical Properties, Weathering Processes, Emergency Response, and Recovery - Zhong, Xiaomei; Li, Pu; Lin, Xiaoyu; Zhao, Zeyuan; He, Quan (Sophia); Niu, Haibo; Yang, Jie (Frontiers in Environmental Science, 2022)
Bitumen, an unconventional crude oil, has received much attention with the increasing consumption and the shrinking storage of conventional crude oils. Bitumen is highly viscous and thus is commonly diluted for transportation purposes. Spills of diluted bitumen could occur during the transportation from reservoirs to refineries via pipeline, rail, and marine vessel. Although some laboratory and numerical modelling studies have been contributed to study the spill of diluted bitumen from different aspects, there is no systematic review in the field yet. Therefore, this study firstly conducted the review on different types of diluted bitumen based upon their physicochemical properties, following by their weathering processes including spreading, evaporation, emulsification, photooxidation, biodegradation and sinking. Secondly, the numerical modelling on the fate and behavior of spilled diluted bitumen were summarized and analyzed. Finally, the techniques for spilled oil recovery were discussed, as well as the disposal/treatment of oily waste. Currently, rare attempt has been made to turn the recovered oily waste into wealth (reutilization/valorisation of oily waste). Using the recovered oily waste as the feedstock/processing medium for an emerging thermochemical conversion technique (hydrothermal liquefaction of biomass for crude bio-oil production) is highly recommended. Overall, this paper summarized the state-of-art knowledge of the spill of diluted bitumen, with the hope to create a deep and systematic understanding on the spill of diluted bitumen for researchers, relevant companies, and decision makers.